Rancang Bangun Aplikasi Pengelolaan Data Customer Dan Monitoring Kinerja Marketing Berbasis Mobile - Farid Akbar Arianta; Arifin Puji Widodo; Teguh Sutanto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
Abstract PT. Federal International Finance (FIF) Nganjuk branch is one branch of PT. Federal Internatuonal Finance, Inc. is engaged in the retail motorcycle financing business and electronic equipment. In the process of financing, one of which relates directly to the customer is marketing. At the time of serving the customer in the field, the problems often faced by marketing that marketing can not check the status of customer data such as pengeekan member and previous arrears, do add a new customer, to process the transaction (in this case the application process until the approval of financing), displays information about the data traffic to the dealer / store, the number of incentives, and the target number of transactions received, that all these can not be done directly in the field saaat. In addition, another problem encountered is the monitoring process will be marketing a visit to the dealer / shop and monitoring achievement of the targets of marketing can not be properly monitored by the admin .Based on all the exposure of the above problems, it takes an application that can perform customer data management, including customer data-checking process, and can add new customer transaction process, and can display information on the number of transactions, the number of targets and the amount received by marketing incentives, which can be processed directly when marketing is the field, as well as can be. make the process of monitoring the performance of marketing is done by the admin. Since the majority of marketing is the mobile phone users, the author tries to build an application "Customer Data Management and Monitoring Performance-based mobile marketing" to answer the above requirements. As a result of the implementation of the Customer Data Management applications and mobile-based Marketing Performance Monitoring has been done, marketing can make the process of checking customers' data, add new customer, and transaction processing to financial filings with the approval of retail financing directly through mobile devices are carried in this case is mobile. In addition, the admin can monitor traffic and monitor the achievement of the target marketing marketing by using applications that are in the office. Keywords: Customer, Marketing, Data Management, Monitoring, Mobile